ANALISIS SEGMENTASI PASAR PADA GULE KEPALA IKAN BANK JO JALAN JENDERAL SUDIRMAN N0 40 BANTUL YOGYAKARTA - Mukhlis Apriadi; Fitroh Adhilla (Jurnal Fokus Manajemen Bisnis, 2013)
This research used an object of Gule Kepala Ikan (Head Fish Curry) of Bank Jo as its research object. This research was aimed to know cluster shaped in Gule Kepala Ikan Bank Jo using demographic and behavioral variables. Population in this research was customers of Gule Kepala Ikan Bank Jo. Samples used numbered 150 respondents, while its sample taking usedaccidental sampling and purposive sampling techniques. Data used in this research was in form of primary data. Primary data was directly obtained from customers by distributing questionnaires fulfilled by Gule Kepala Ikan Bank Jo customers who were purchasing during this research performed. Variable used in this research was demographic and behavioral variables using a gender attribute, age, marital status, attitudes in selecting menu, income, tribes and occupation. Data collected was then processed using a direct marketing method. The data processing result of Gule Kepala Ikan Bank Jo respondents formed into two clusters with a still-waek model quality. Cluster 1 formed by 51 respondents by a cluster size of 34%, while cluster II formed by 99 respondents by a cluster size of 66%.